THE EFFECT OF JAMAICAN CHERRY LEAF EXTRACT (MUNTINGIA CALABURA L.) AND CANDESARTAN COMBINATION ON BLOOD PRESSURE IN HYPERTENSION MODEL RATS. - Al-Sharifa Ajiwibowo, Aisha
High blood pressure, or hypertension, is one of the most common cardiovascular diseases in the world. According to the World Health Organization, a person is considered hypertensive if their blood pressure is more than 140/90 mmHg. Hypertension can be controlled by lifestyle changes and the use of drugs that can lower blood pressure. The drugs used can be antihypertensive drugs, herbal medicines, or a combination of both. This study was conducted to analyze the effect of administering ethanol extract of Jamaican cherry leaves (EEDK) when combined with antihypertensive drugs from the angiotensin receptor blocker (ARB) group, such as candesartan. The animals used in this study were dexamethasone-induced hypertensive male Wistar rats. Dexamethasone was given 0.5 mg/kg body weight subcutaneously for 10 days. The combination of EEDK and candesartan (1:1) was given orally for 7 days without stopping dexamethasone induction. Blood pressure was measured noninvasively using the CODA® tail-cuff blood pressure system at t0, t10, t13, and t17. The groups of candesartan cilexetil 5 mg/kg bw, EEDK 100 mg/kg bw, and the combination of candesartan cilexetil- EEDK (1:1) were able to reduce systolic blood pressure by 35.71 ± 10.05; 36.35 ± 3.98; and 43.06 ± 7.30 mmHg, respectively. The decrease in diastolik blood pressure was 30.06 ± 4.98; 27.25 ± 6.96; and 22.07 ± 4.35 mmHg, respectively. The combination of candesartan and ethanol extract of Jamaican cherry leaves was able to reduce blood pressure faster than the use of candesartan or a single extract.